Long‐term safety and efficacy of bimatoprost solution 0·03% application to the eyelid margin for the treatment of idiopathic and chemotherapy‐induced eyelash hypotrichosis: a randomized controlled trial. (1st May 2015) - Glaser, D.A.; Hossain, P.; Perkins, W.; Griffiths, T.; Ahluwalia, G.; Weng, E.; Beddingfield, F.C.
Summary: Background: Bimatoprost ophthalmic solution 0·03% is approved in several countries for the treatment of eyelash hypotrichosis. Previous trials were limited to 4 months of treatment and primarily idiopathic hypotrichosis. Objectives: To evaluate the long‐term safety and efficacy of bimatoprost in patients with idiopathic or chemotherapy‐induced hypotrichosis. Methods: This multicentre, double‐masked, randomized, parallel‐group study included two 6‐month treatment periods [treatment period 1 (TP1) and treatment period 2 (TP2)]. Patients with idiopathic hypotrichosis were randomized to three treatment groups: (i) bimatoprost (TP1 and TP2); (ii) bimatoprost (TP1) and vehicle (TP2); and (iii) vehicle (TP1) and bimatoprost (TP2). Patients with chemotherapy‐induced hypotrichosis were randomized to two treatment groups: (i) bimatoprost or vehicle (TP1) and (ii) bimatoprost (TP2). Primary end point was a composite of at least a one‐grade improvement in investigator‐assessed Global Eyelash Assessment and at least a three‐point improvement in patient‐reported Eyelash Satisfaction Questionnaire Domain 2 at month 4. Secondary measures included digitally assessed eyelash characteristics. Results: The primary efficacy end point was met in both populations (idiopathic responder rate was 40·2% for bimatoprost vs. 6·8% for vehicle; postchemotherapy responder rate was 37·5% for bimatoprost vs. 18·2% for vehicle). Efficacy by month 6 was maintained (idiopathic) or enhanced (postchemotherapy) at 12 months. Treatment effects were maintained for approximately 2 months but markedly diminished 4–6 months following treatment cessation in patients with idiopathic hypotrichosis. No drug‐related serious adverse events were reported. Conclusions: Daily treatment with bimatoprost ophthalmic solution 0·03% for 1 year was effective and well tolerated in patients with idiopathic and chemotherapy‐induced hypotrichosis.